On the Majalengka Sundanese: Lexical Variations and Morphology - Purwitasari, Ana (Jurnal IKADBUDI, 2024)
Majalengka Sundanese has been heavily influenced by Indonesian and Javanese for having a Javanese enclave. On the contrary, Indonesian influences vocabulary spoken mainly in Majalengka, Sukahaji, Panyingkiran, Cigasong and Kadipaten sub-districts as those regions are located near from the city centre of Majalengka Regency. Majalengka Sundanese words got shaped by Javanese are natively uttered in the Javanese enclave, referring to Patuanan rural village in Leuwimunding sub-district. Those are also uttered in Jatitujuh rural village in Kertajati sub-district and Parapatan rural village in Sumberjaya sub-district for sharing border with Indramayu and Cirebon regencies as home of Javanese speakers. The data were gathered by interviewing natives. Those words altered by Javanese include (1) pertelon "˜T-intersection', (2) enok "˜child (to call a girl)', (3) sugih "˜wealthy' and (4) waras "˜get well'. Moreover, the Majalengka Sundanese words modified by Indonesian add up to 26 words. Compared to Standard Sundanese, Majalengka Sundanese has also distinct vocabulary characterized Majalengka people, amounting to 55 words. Morphologically, Majalengka Sundanese differs from Standard Sundanese for having these suffixes, e.g. (1) nga-, (2) nga-keun and (3) nga-an to replace suffixes m-, m-keun and m-an which are frequently found in Standard Sundanese to form particular words. Nevertheless, there are several exceptions found in the specific lexicons.